Anion Conductance Behavior of the Glutamate Uptake Carrier in Salamander Retinal Glial Cells - Billups, Brian (J Neurosci, 1996)
Glutamate uptake is driven by the cotransport of Na(+)ions, the countertransport of K(+) ions, and either the countertransport of OH(−) or the cotransport of H(+) ions. In addition, activating glutamate uptake carriers has been shown to lead to activation of an anion conductance present in the carrier structure. Here we characterize the ion selectivity and gating of this anion conductance. The conductance is small with Cl(−) as the permeant anion, but it is large with NO(3)(−) or ClO(4)(−) present, undermining the earlier use of NO(3)(−) and ClO(4)(−) to suggest that OH(−) countertransport rather than H(+) cotransport helps drive uptake. Activation of the anion conductance can be evoked by extra- or intracellular glutamate and can occur even when glutamate transport is inhibited. By running the carrier backward and detecting glutamate release with AMPA receptors in neurons placed near the glial cells, we show that anion flux is not coupled thermodynamically to glutamate movement, but OH(−)/H(+) transport is. The possibility that cell excitability is modulated by the anion conductance associated with glutamate uptake suggests a target for therapeutic drugs to reduce glutamate release in conditions like epilepsy.